Review of Experience of Family Medicine in Europe and Central Asia, Volume 2, Armenia Case Study - World Bank (Washington, DC, 2012)
This report summarizes the findings of four case studies that review the experience of family medicine in Europe and Central Asia (ECA) Region. It is part of a study comprising five volumes that review the experience of family medicine in four countries in ECA--Armenia, Bosnia and Herzegovina, Kyrgyz Republic and Moldova. The report reviews the experience, draws lessons, and establishes an evidence base for detailed analysis. The study presents best practices for policy dialogue and future investments by the World Bank and other financial institutions. The detailed case studies compare these countries and draw common themes and issues. Comparisons are made with best-developed or existing models in the OECD and other countries in the Europe and Central Asia Region that have already undertaken family medicine reform.